Alterations of the paired maternal fecal microbiota and neonatal meconium microbiota in newborns from pregnant women with hypertensive disorders - Yang, Heng; He, Zhijiang; Lai, Jianfen; Yang, Jing; Huang, Qianrong; Chang, Ying; Tian, Mingyuan; Huang, Hongli (Frontiers in Microbiology, 2025)
BackgroundHypertensive disorders of pregnancy (HDP) pose significant risks to both maternal and fetal health and have been associated with alterations in the maternal gut microbiota. However, the impact of HDP on neonatal microbiota remains poorly understood. This study aimed to characterize the gut microbiota of pregnant women with HDP and evaluate its potential influence on the meconium microbiota of their newborns.MethodsA cohort of 67 pregnant women, including 36 diagnosed with HDP (HDP group) and 31 healthy, age-matched controls (HC group), along with their offspring, were recruited. Fecal samples collected during the third trimester and meconium samples from the newborns were subjected to microbial community profiling via 16S rRNA gene sequencing.ResultsPrincipal coordinate analysis (PCoA) based on Bray-Curtis distances revealed significant differences in microbial community composition between the HDP and HC groups in both maternal and neonatal samples. Subgroup analyses, stratified by HDP severity and medication use, further delineated distinct microbial profiles relative to controls. Notably, both maternal and neonatal microbiota in the HDP group exhibited increased abundances of Enterobacter, Klebsiella, and Sphingomonas, coupled with a reduction in Acidovorax, Azospirillum, Caulobacter, Flavobacterium, Magnetospirillum, and Rubrivivax compared to the HC group. Moreover, the P4-PWY pathway, which is involved in the biosynthesis of L-lysine, L-threonine, and L-methionine, was differentially represented in both maternal and neonatal microbiota in the HDP group. These parallel patterns suggest an intergenerational concordance associated with HDP.ConclusionThis study demonstrates significant alterations in the microbial communities of both maternal fecal and neonatal meconium samples in the context of HDP. The findings highlight the importance of further research to elucidate the long-term health implications of HDP-associated microbiota shifts on offspring.